The University as a Being-historical Object: the Experience of M. Heidegger - M. B. Mitlyanskaya (Высшее образование в России)
The article is based on the historical and philosophical analysis of fragments of Martin Heidegger’s concept called “Seinsgeschichte”, in which the philosopher considered the phenomenon of the university and the current situation of sciences. Their condition, accord- ing to the philosopher, is a direct consequence of the comprehensive extinction of the tradi- tion of European thinking, originating in the era of Platonism. The main signs of the era of the “decline of metaphysics” are the primacy of form over content, the “factory” production of university personnel and products of scientific activity, the rejection of comprehension as an urgent necessity and the total domination of the utilitarian approach to knowledge. Heidegger has no formed positive project to overcome the current state of affairs. Firstly, because he had an unsuccessful experience of rectorship, including a fruitless attempt to put into practice his philosophical ideas, to which part of this article is devoted. Secondly, since the rejection of uni- versal methods, ready-made answers and unshakable truths becomes an integral part of his late philosophy, since they lull thinking and lead a person away from fruitful doubt. A deep analysis of the origins of the crisis of the European University allows us to take a different look at the side effects of industrialization and digitalization of modern society and outline possible ways to resolve it in the future.